The Comparasion Between Science Classes and Social Classes Students in Translating Reading Passages - Ilham Ilham (Linguistics and ELT Journal, 2021)
Reading and language skill states clearly that in translating the texts, the translator absolutely needs three things. Firstly, the texts to be translated, secondly, the excellent dictionaries or idiom lists and the last is the translator’s individual ability in conveying the natural meaning of the text into the other form, style, language, term and so forth which is succesfully done systematically but retaining the original sense. The purpose of this research is to know the comparison between Science Classes and Social Classes students in translating reading passages to the second year students’ of SMAN 1 Labuapi in Academic Year 2014/2015. The population of the research was the third year students of SMAN 1 Labuapi. They were all two classes: class II IPA which total number 20, and class II IPS which total number 20 students, so the total population number were 40 students. They supposed to have been actively joinied the English lessons. This population homogeneous, because they all in the same level either regarding to their knowledge or their experiences. Comparative research or analysis is a broad term that includes both quantitative and qualitative comparison of social entities. The method of the study applied here is a comparative research method which include in ex-post-facto research design. This was inspired by the data which is needed to prove’ the hypothesis. Therefore, a simple treatment might be needed, as the reaserch described the existence of the different departements in translating some reading texts/passages at the third year students of SMAN 1 Labuapi in Academic Year for the data collection, the writer applied testing method. And the data would be analysed through basic statistical computation. After getting the last value of t-test with the t-table, it’s found that t-test = 2.40 with the t-table = 2.70 (0.01%), and t-test = 2.40 with the t-table = 2.02 (0.05%). It means that t-table is greater than t-test, it also means that the alternative hypothesis (Ha) which read that “the students of Science Classes program have better achievement in translating reading passages of SMAN 1 Labuapi in Academic Year 2014/2015 is accepted. While the Null Hypothesis, which sound “ the students of Social Classes program have better achievement in translating reading passages of SMAN 1 Labuapi in Academic Year 2014/2015 is rejected.